Genetic and Environmental Determinants of Beef Quality—A Review - Sakowski, Tomasz; Grodkowski, Grzegorz; Gołebiewski, Marcin; Slósarz, Jan; Kostusiak, Piotr; Solarczyk, Paweł; Puppel, Kamila (Frontiers in Veterinary Science, 2022)
The flavor, quality, and composition of beef changes with the cattle diet regimen. The quality of meat varies, and that variability is determined by both individual and environmental factors: age, breed, live weight, fatness degree, plane of nutrition, and concentrate/roughage ratio. The strategy for the rearing and feeding of cattle for slaughter should therefore aim at reducing the saturated fatty acid content and increasing the polyunsaturated fatty acid and monounsaturated fatty acid levels. Many diseases in humans, like atherosclerosis and cardiovascular diseases, are associated with dietary fat, and their development process could take a year, the results of which can be a shorter life and its lower quality. The objective of this review was to describe the factors affecting the meat quality and fatty acid profile of the intramuscular fat of European cattle fed various diets.